Let f(x)= 9x-2 and g(x)= -x+3. Find f(g(x)).
This is what I have so far:
g(x)= -x+3
f(g(x))= f(-x+3)
f(x)= 9x-2
f(g(x))= 9x-2( )
f(g(x))= 9x-2(-x+3) <--Here you have to multiply: 9x* -x, then 9x*3, then -2*-x, then -2*3.
f(g(x))= -9x^2+27-3x+6 <-- I am almost done but I don't know how to simplify it.
This is what I have so far:
g(x)= -x+3
f(g(x))= f(-x+3)
f(x)= 9x-2
f(g(x))= 9x-2( )
f(g(x))= 9x-2(-x+3) <--Here you have to multiply: 9x* -x, then 9x*3, then -2*-x, then -2*3.
f(g(x))= -9x^2+27-3x+6 <-- I am almost done but I don't know how to simplify it.